The History of Luxurious Clothing for Court Women in the Umayyad State and Its Impact on Daily Life (41-132 AH / 661-750 CE) - bin Yahya, Ibtisam Salim; Bashinah, Mohammed Omar (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The research aims to explore the evolution of fashion by studying how luxury clothing for court ladies developed during the Umayyad period and the impact of cultural and social factors on these developments, including external influences. The study seeks to analyze the materials used in creating luxurious garments and the techniques employed in their embroidery and embellishment. It also aims to highlight the role of women in the court in social and political life, and how their clothing contributed to enhancing their status. Additionally, the research intends to compare luxury clothing in the Umayyad state with prevailing styles in previous and subsequent periods to understand cultural transformations. The methodology includes historical descriptive analysis, comparative analysis, and textual and narrative analysis related to the topic. Among the key findings of the research is that the evolution of fashion, represented by the luxury clothing of court ladies, showed a remarkable development influenced by various cultures due to trade, industry, and interaction.